Finite Element Analysis of the Dump Truck Driving Axle Housing based on ADAMS & ANSYS WORKBENCH Virtual Environment - Zhang Lijuan (Jixie chuandong)
To further shorten the product development cycle of dump truck driving axle housing and improve the production efficiency,a dump truck drivngaxle design method is presented based on the practical road test parameter and the ADAMS and AWB common used in finite element analysis,the law of the axle housing stress and strain conditions under the practical road test parameter is studied,and the influence law of the frequency of load and size of load on the axle housing life is analyzed.The results show that dump truck driven axle housing larger stress area concentrated on the right and left axle and wheel connection area,the dump truck driven axle fatigue life cycles and damage factor minimum are in axle housing wheel area,the influence of load amplitude changes on the life of the axle housing is small,the influence of load frequency change on the axle fatigue life.